A Stocking diagram for silvicultural implications in Scots Pine (Pinus sylvestris L.) stands - Kara, Ferhat (Kastamonu University, 2018)
Aim of study: Residual stand densities are commonly defined using basal area (m2 ha-1) (BA) and number of trees per hectare (TPH) when using even-aged silvicultural methods such as clearcutting and shelterwood methods in Scots pine (Pinus sylvestris L.) forests. However, it has been stated that absolute density measures such as BA and TPH are not the most useful indexes because growing space at a given BA or TPH varies with average tree diameter. Therefore, silvicultural management tools such as stocking charts (SC) and density management diagrams (DMD) have seemed to be more useful when allocating growing space to achieve a broad range of silvicultural objectives in even-aged stands. Given the importance of stand density on the regeneration success and growth of Scots pine, and given the shortages of absolute density measures (i.e. BA and TPH), a density diagram would be a useful tool for this tree species as well. Thus, in this study, a stand stocking diagram (SD) was developed for Scots pine stands. Material and Methods: Two published equations developed from open grown Scots pine trees, and from normal Scots pine stands were utilized to determine the minimum density of full site occupancy and the average maximum density, respectively. The form of the diagram follows Gingrich stocking chart. Main results: The A-line on the diagram represents the average maximum density where trees, on average, have the minimum growing space needed to survive. The B-line represents the lowest density where canopy closure can occur and is the minimum stocking necessary for full site occupancy or canopy closure. Consistent with a published Scots pine DMD, there is biological relevance and utility to the stocking diagram created in this study. Highlights: With the stocking diagram presented in this paper, regeneration and tending applications will be more practical in Scots pine forests because available growing space will be well-determined and utilized using the diagram.
Keywords: Density; even-aged; management tools; silviculture; Eşit-yaşlı; Silvikültürel araçlar; Silvikültür; stok diyagramı; 2. Zero hunger; 15. Life on land